Downflow bubble column electrochemical reactor (DBCER): In-situ production of H2O2 and O3 to conduct electroperoxone process. Issue 4 (August 2021) - Santana-Martínez, Germán; Roa-Morales, Gabriela; Gómez-Olivan, Leobardo; Peralta-Reyes, Ever; Romero, Rubí; Natividad, Reyna
Abstract: In the context of water remediation, advanced oxidation processes have been proven to be an effective solution. In most of the cases, however, the reaction systems are usually highly expensive, because of the addition of chemical substances or energy consumption. This usually constrains their application at an industrial scale. This has motivated several researchers to develop technologies able not only to intensify the processes but able also to increase the sustainability of the whole process. In this context, this work aimed to assess a relatively novel technology, a Downflow Bubble Column Electrochemical Reactor (DBCER), in the mineralization of a rather typical organic pollutant, phenol. The studied variables were: current density (20–60 mA/cm 2 ), electrolyte concentration (0.025–0.1 M), liquid recirculation rate (4.7 and 6 L/min) and pH (3 and 7). The response variables were total organic carbon (TOC), phenol and by-products concentration, oxidant species concentration (O2, H2 O2 and O3 ). It was demonstrated that the DBCER with BDD electrodes allows not only the production of OH, but also the in situ production of O2, H2 O2 and O3 (without the addition of any gas) and more importantly their utilization to conduct an electro-peroxone process. The highest mineralization degree was around 75% under pH 3, 60 mA/cm 2, 4.7 L/min and an electrolyte concentration of 0.05 M. Under these conditions, it was figured out that the phenol oxidation occurs mainly by ozone attack and the main remaining compound was oxalic acid. Although at pH 7 the mineralization degree was lower than at pH 3, it was demonstrated by a biotoxicity study on Cyprinus carpio that the original toxicity was significantly decreased. Graphical Abstract: ga1 Highlights: DBCER allows to conduct E-peroxone with in situ reagents production. O3 and H2 O2 are produced in situ with BDD and used to mineralize phenol. DBCER reduces reagents consumption and eliminates gas waste. Electro-peroxone of phenol at pH 7 eliminates toxicity on Cyprinus carpio .